2016
DOI: 10.1007/s00784-016-1815-2
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue augmentation procedures at second-stage surgery: a systematic review

Abstract: The localization in the jaw and the clinical situation are crucial for the decision which second-stage procedure should be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 82 publications
2
70
1
4
Order By: Relevance
“…A precise time of surgery, in particular second stage surgery or re-entry, could help achieving the best results, as suggested by a literature review on vestibuloplasty techniques by Bassetti et al [32]. Unfortunately studies involving only an apically repositioned split thickness flap are very limited, but it has been shown that this technique is more effective in the maxilla, where a bigger reservoir of keratinized mucosa is present [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise time of surgery, in particular second stage surgery or re-entry, could help achieving the best results, as suggested by a literature review on vestibuloplasty techniques by Bassetti et al [32]. Unfortunately studies involving only an apically repositioned split thickness flap are very limited, but it has been shown that this technique is more effective in the maxilla, where a bigger reservoir of keratinized mucosa is present [32].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately studies involving only an apically repositioned split thickness flap are very limited, but it has been shown that this technique is more effective in the maxilla, where a bigger reservoir of keratinized mucosa is present [32]. …”
Section: Discussionmentioning
confidence: 99%
“…With respect to soft tissue augmentation surgery, different preferred materials and timings have been reported in various studies and reviews (Bassetti, Stähli, Bassetti, & Sculean, ; Esposito, Maghaireh, Grusovin, Ziounas, & Worthington, ; Fu et al., ; Lin et al., ; Rotundo et al., ; Thoma, Buranawat, Hammerle, Held, & Jung, ; Thoma et al., ; Thoma, Muhlemann et al., Wu et al., ). Over the years, autogenous soft tissue graft has been regarded as a gold standard for peri‐implant soft tissue augmentation, although some have claimed that a new xenogenic collagen matrix might achieve comparable outcomes (Cairo et al., ; Zeltner, Jung, Hammerle, Husler, & Thoma, ).…”
Section: Introductionmentioning
confidence: 99%
“…Often in cases of bone atrophy, keratinized mucosa may not be present, and techniques to increase the amount of keratinized mucosa may be performed during implant installation or second‐stage surgery. The presence of keratinized mucosa has a positive effect on peri‐implant tissue health . In a systematic review, Bassetti et al found that patients with sites with a width of <2 mm of keratinized mucosa developed discomfort during brushing more easily and also exhibited dental plaque accumulation and peri‐implant soft tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%